Marine New Quality Productive Forces Empower Marine Environmental Governance: Theoretical Logic, Key Issues and Future Path - QUAN Yongbo; JIN Jilan (Haiyang Kaifa yu guanli)
Enhancing the comprehensive capacity of marine environmental governance holds significant implications for the construction of a maritime power and the promotion of sustainable development of the marine economy. Marine new quality productive forces (MNQPF), characterized by informatization, intelligentization, and greenization, is driving technological innovation, leading to a significant leap in marine productivity, offering a new perspective and potential for China’s marine environmental governance. However, challenges persist in the process of empowering marine environmental governance with MNQPF, including relatively weak basic marine research, difficulties in promoting green technologies, lagging behind in cultivating scientific and technological talents, and the need for enhanced participation in global marine environmental governance. In light of these challenges, this paper is grounded in the concept of MNQPF, proposing to accelerate the promotion of marine scientific and technological innovation development, the dissemination and application of marine green technology development, the advancement of marine scientific and technological talent pool, and active engagement in global marine environmental governance as advancing pathways.